Application of a prefeasibility study methodology in the selection of road infrastructure projects: The case of Manizales (Colombia) - Escobar Garcia, Diego Alexander; Younes-Velosa, Camilo; Moncada-Aristizábal, Carlos Alberto (DYNA, 2015)
Major cities in Colombia are currently generating urban transformation processes that involve the construction of major infrastructures, which mainly look to mitigate the adverse effects of ever-increasing road traffic. In addition, intermediate cities have made great efforts when it comes to urban planning and promote the application of prefeasibility study methodologies to make the appropriate decisions regarding the infrastructures to be built in specific places in the city. This paper discusses the results after applying a prioritization methodology as a comparative tool between two possible road infrastructures in the area of San Marcel in the city of Manizales, Colombia. The best proposal is selected based on the best coverage indicators and variables such as overall construction costs and life span: determined from information generated in traffic simulations.